2021
DOI: 10.52547/qums.14.12.70
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Health Literacy of Elderly Diabetics and Adherence to Treatment, Babol, Iran, 2021

Abstract: Background and Objectives: Non-adherence to treatment in elderly diabetics is associated with several problems. Existing studies have been less addressed the dimensions of treatment adherence in this population. This study examines the relationship between health literacy of elderly diabetics and adherence to treatment.Methods: : This descriptive-analytical study was conducted among 375 randomly selected elderly members of Babol Diabetes Association. Data collection instruments included demographic sheet, abbr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Goli Roshan et al (7) in Iran showed a significant relationship between health literacy and adherence to treatment.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Goli Roshan et al (7) in Iran showed a significant relationship between health literacy and adherence to treatment.…”
Section: Discussionmentioning
confidence: 96%
“…According to regression analysis, the higher the health literacy, the higher the rate of treatment adherence (7). Mehrtak et al (33) in Iran reported the effect of health literacy on adherence to medication, nutrition, and physical activity of patients with type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many unpleasant health-related consequences occur because of poor health literacy. Limited health literacy has been associated with poor health outcomes, detrimental health behaviors, lower patient satisfaction, and in some cases, higher mortality [ 13 ]. Individuals with limited health literacy have trouble understanding the oral and written information provided by physicians, nurses, and insurers, as well as medication instructions, so they cannot achieve the health services they need in healthcare systems.…”
Section: Introductionmentioning
confidence: 99%